A Comparison Study on Traditional Mixtures of Herbal Teas Used in Eastern Mediterranean Area - Obón, Concepción; Rivera, Diego; Fonollá, Elena; Alcaraz, Francisco; Attieh, Latifa (Frontiers in Pharmacology, 2021)
Multipurpose herbal teas with numerous ingredients, in which flowers are the main component, are common in the traditional medicine and pharmacy of Greece and the Eastern Mediterranean countries. In this study, we combine ethnobotany and ethnopharmacology field work techniques and botany and pharmacognosy laboratory methods for the study of traditional herbal mixtures with flowers, we identify their botanical ingredients and record the local medicinal uses of these mixtures, in Greece, Lebanon, Syria, Iran and Turkey. These, and their industrial versions, are analyzed, using morphological and multivariate analysis techniques in order to determine marker species, relevant patterns of combination and local styles. The medicinal properties attributed to the different flowers are discussed in relation with their role in the mixtures. These blends are consumed for their relaxing, digestive, and anti-infective properties. These mixtures are not consumed as a treatment when one is sick but rather to avoid getting sick, as a preventive measure. The formulations can reach forty ingredients (sarantha in Greek, arbain in Arabic language of Palestine), usually entire or coarsely chopped in the more traditional formulations, leading to extreme variability of individual doses. We ask what biological signification this randomness can have. To give an answer requires new and more comprehensive pharmacological approaches. The flowers of Rosaceae, Asteraceae, Lamiaceae, Malvaceae and Fabaceae species characterize these mixtures in which other materials (roots, leaves, and fruits) and other species are present as well. Flowers of some species, particularly of Fabaceae, are exclusively used in mixtures, and their use in monospecific herbal teas is not yet recorded. We draw attention on the urgent need in exhaustively recording in Greece and the Near East, the formulation and use of traditional herbal mixtures and their numerous local variants. To consider these mixtures and the contribution of flowers (most mixtures receive the general name of tea of flowers) merits further extensive study.